Deep Learning of Knowledge Graph Embeddings for Semantic Parsing of Twitter Dialogs - Heck, Larry (The 2nd IEEE Global Conference on Signal and Information Processing (DRAFT), 2014)
This paper presents an unsupervised neural knowledge graph embedding model and a coherence-based approach for semantic parsing of Twitter dialogs. The approach learns embeddings directly from knowledge graphs and scales to all of Wikipedia. Experiments show a 23.6% reduction in semanticparsing errors compared to the previously best reported results.